Human Resource Development Strategies For Mental Health Program Officers: A Case Study in Sukabumi City - Florens Liesna Hasudungan Marpaung; Abdul Rahman; Septiana Dwiputrianti; Hafid Aditya Pradesa (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2026)
Mental health is a priority in Indonesia’s development, yet primary care faces significant human resource (HR) challenges. In Sukabumi City, 2024 service coverage for severe mental disorders (ODGJ) reached 95.9%, falling short of the 100% Minimum Service Standard (SPM). This qualitative case study evaluates manager performance and formulates HR development strategies using the Miles and Huberman framework alongside IFAS, EFAS, and SWOT analysis. The study concludes that Sukabumi occupies an Aggressive-Growth (Quadrant I) position. While performance is currently hindered by internal structural bottlenecks—notably an 80% dual-role burden and clinical competency gaps—these are outweighed by strong internal commitment and significant external opportunities, such as Mayor’s Regulation No. 126/2025. To bridge the performance gap, the study recommends a strategic HRD roadmap: formalizing the Community Mental Health Task Force (TPKJM) at the sub-district level to redistribute workloads, implementing SKKNI-based certified training, and optimizing the SIMKESWA platform for digital monitoring. Transitioning from fragmented, multi-tasking roles to a specialized, competency-based system is essential. By integrating these strategies, Sukabumi City can transform program officers into strategic coordinators, ensuring the sustainable achievement of the 100% national mental health mandate.